Sebaran C Organik Tanah pada Penggunaan Lahan Pertanian Pangan di Kabupaten Situbondo - Fadhila Syaqwa Ahqmara (Fakultas Pertanian, 2025)
Soil organic carbon (C-organic) is a major component of soil organic matter that plays a crucial role in maintaining soil fertility and agricultural land productivity. Before 2019, the C-organic content in agricultural soils of Situbondo Regency was generally below 1%. However, since the implementation of the organic fertilizer program in 2019, many studies have shown a significant increase in C-organic levels due to the growing awareness of farmers in using organic fertilizers. This study aims to determine the distribution of soil C-organic in agricultural land use in Situbondo Regency, quantify the increase in C-organic, analyze its relationship with observed physical and chemical soil properties, and provide a reference for the optimal organic fertilizer requirements in the region. This research employed the K-means Cluster method representing paddy fields, drylands, and mixed shrub drylands, using the stratified sampling technique at a soil depth of 0–20 cm. Laboratory analyses included measurements of C-organic, pH, total nitrogen (N total), cation exchange capacity (CEC), base saturation, bulk density, particle density, soil texture, total pore space, and Atterberg limits. The laboratory analysis of C-organic was conducted using the Kurmis and Walkley & Black methods. Data were analyzed using ANOVA and correlation tests to determine the differences and relationships among variables. Therefore, increasing the application of organic matter, adjusting fertilizer dosages, implementing conservation agriculture, and providing technical assistance to farmers are necessary to enhance C-organic content and maintain the sustainability of agricultural land in Situbondo Regency.
Reuploud Repository hasyim Juni 2026 Approved by Teddy
Keywords: Soil Organic Carbon; Land Use; Situbondo Regecy; Orgabic Fertillizer